OPTIMIZATION OF DIGITAL FINANCE FOR RECIPIENTS OF SOCIAL ASSISTANCE FAMILY HOPE PROGRAM(PKH) IN WARUREJA DISTRICT REVIEWED FROM THE THEORY OF ASHABIYYAH - Nabila, Anissa Putri; Hermawan, Hendri; Shulthoni, Muhammad; Andrean, Rizky (Ekonomi Islam, 2025)
Research aims: This study aims to analyze the optimization of digital finance in the implementation of the Family Hope Program (PKH) in Warureja District, using Ibn Khaldun’s Ashabiyyah theory as an analytical framework. Design Methodology/Approach: A qualitative field research approach was applied, involving interviews and observations with the Village Head, five PKH recipients, and one PKH facilitator in Demangharjo Village, Warureja District, Tegal Regency. Primary and secondary data were collected to gain a comprehensive understanding of the community’s experiences with digital finance systems. Research findings: The results reveal that digital finance has enhanced efficiency and transparency in the distribution of social assistance. Recipients reported faster access to aid and improved communication with facilitators, although many still struggle with using digital tools due to low digital literacy. Notably, the community's strong social cohesion (Ashabiyyah) facilitated mutual support among PKH members in adapting to technological changes. Challenges such as fear of data misuse and limited understanding of ATM/mobile banking were mitigated through collective learning and socialization activities. Theoretical Contribution/Originality: This study offers a novel application of Ashabiyyah theory in the context of digital finance and social assistance, showing how social solidarity can support technological adaptation in rural communities. Practitioners/Policy Implications: Findings suggest the need for local governments to invest in digital infrastructure and provide regular, community-based digital literacy training. Facilitators should adopt participatory approaches to strengthen recipient engagement. Encouraging collective learning among PKH recipients can further reinforce program success. Research Limitations/Implications: The study is limited to a single village and does not incorporate broader Islamic references (Qur’anic verses or Hadiths). Future research should expand the geographical scope and explore deeper religious-theoretical foundations to enrich analysis and policy recommendations.